Integrating critical thinking into language learning: A DDL and TBLT-based syllabus for Indonesian schools - Erlangga Erlangga; Haidir Algi Ghaffar Faridha; Muhammad Fahresy Alfariz; Radhiyatul Jamilah (Universitas Muhammadiyah Malang, 2025)
This study aims to analyze possible challenges and benefits of combining critical thinking guidance toward teaching and language learning by combining Task-Based Language Teaching (TBLT) and Data-Driven Learning (DDL) systems to create a syllabus which could be utilized in an Indonesian language school setting. The study utilized a qualitative research synthesis (QRS) approach by using a dynamic framework by Chong & Reinders (2020), The study reviewed 25 studies on Critical Thinking, DDL, and TBLT published within the past five years, using backward and forward snowballing techniques and inclusion criteria. The result concludes beneficial effects from both DDL and TBLT on the subject of language learning understanding in the context of EFL/ESL, the integration does not only enhance language proficiency but also equip learners with valuable cognitive skills that extend beyond language learning, such as computer literacy and learner autonomy. DDL has enhanced student’s metalinguistic awareness, allowing them to critically examine the structure of language. Furthermore, focusing on form tasks in DDL enhances comprehension of language usage, while engaging with authentic materials increases computer literacy as well as motivation. On the other hand, use of TBLT’s technological and authentic subject matters resulted in enhanced linguistics abilities, comprising listening, writing, speaking, and reading. The indications of this paper are immense for the academic area of ELT and future studies. Linguistic instructors may modify and utilize this paper’s final syllabus design to encourage critical thinking and language proficiency, and future studies might focus on critical thinking's long-term impacts.